Influence of volatile organic compounds of varnish-and-paint materials on the workers organism on the industrial enterprises - Архіпова, Г.І.; Падун, А.О.; Погосова, К.Т. (Proceedings of National Aviation University (archive), 2010)
In article describes the reasons of air contamination in working area of endustrial enterprises, defines main ways of incoming and mechanism of action of volatile organic compounds of paintwork material on the organisms of workers.